2009
DOI: 10.1111/j.1365-2486.2008.01840.x
|View full text |Cite
|
Sign up to set email alerts
|

Climatic changes and 13‐year trends in stream macroinvertebrate assemblages in New South Wales, Australia

Abstract: Over the period from 1994 to 2007, air and water temperatures in the Australian state of New South Wales (NSW) increased while rainfall and river flows declined. Data on the occurrence of stream macroinvertebrate families in bioassessment samples collected in NSW during this period were examined to see whether a biological response to these climatic and hydrological trends could be discerned. Multiple logistic regression was used to test for long-term trends in the probability of detection of individual macroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
103
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(112 citation statements)
references
References 61 publications
8
103
0
1
Order By: Relevance
“…Additionally, knowledge of the environmental requirements and distribution ranges of the species in this kind of harsh environment is useful to identify biological variations when climate changes occur, and to distinguish bioindicator species of the health status of freshwater ecosystems. Several studies have demonstrated biological (composition, distribution, phenology) variations with climate change (Hassall et al, 2007;Chessman 2009). Because of this, features of individual species (like thermal tolerances, rheophily, habitat selection, among others) require to be determined to recognise those species most at risk of extinction.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, knowledge of the environmental requirements and distribution ranges of the species in this kind of harsh environment is useful to identify biological variations when climate changes occur, and to distinguish bioindicator species of the health status of freshwater ecosystems. Several studies have demonstrated biological (composition, distribution, phenology) variations with climate change (Hassall et al, 2007;Chessman 2009). Because of this, features of individual species (like thermal tolerances, rheophily, habitat selection, among others) require to be determined to recognise those species most at risk of extinction.…”
Section: Discussionmentioning
confidence: 99%
“…Climate change may affect environmental conditions, and subsequently bioinvasions, by altering the pool of potential invaders and influencing the chance that non-native species will establish (Rahel and Olden 2008). Studies on the effects of climate change in lake and river systems have shown changes in freshwater species composition and diversity for fish (Buisson et al 2008;Daufresne and Boet 2007) and macroinvertebrates (Burgmer et al 2007;Chessman 2009;Daufresne et al 2004;Mouthon and Daufresne 2006). Abiotic changes in river systems typically include increases in water temperature, river dynamics and salinity (Gornitz 1991;Webb 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies report on aspects of meteorological and hydrological fluctuations in freshwater ecosystems (ZHANG et al, 2005;JIANG et al, 2006;KEIL et al, 2008), but few have explicitly linked them to biological changes. However, in Europe, America, and Oceania, several studies have ascribed long-term shifts in freshwater communities to directional climatic changes (DAUFRESNE et al, 2004;Harper and PECKARSKY, 2006;Durance and ORMEROD, 2007;Haidekker and HERING, 2008;CHESSMAN, 2009). However, very little information is available on the effects of climate changes on freshwater macroinvertebrate communities in Asia (DUDGEON, 2007;VASS et al, 2009).…”
mentioning
confidence: 99%